The effectiveness of ecdysteroid hormones through feed in increasing growth and reproductive performance of mangrove crab (Scylla sp) - Mahdaliana, Mahdaliana; Salamah, Salamah; Muliani, Muliani (Universitas Malikussaleh, 2022)
This study aims to determine the effect of feeding containing ecdysteroid hormones to increase the growth and reproduction of mangrove crabs so as to produce optimal reproduction of mangrove crabs. This research was conducted from August to October 2021 at the Hatchery and Cultivation Technology Laboratory. The method used in this study was a non-factorial completely randomized design (CRD) with 4 treatments and 3 replications, the addition of ecdysteroid hormone 5.50 ml, 7.50 ml, 9.50 ml and 0 ml. The results showed that the addition of ecdysteroid hormones to the feed significantly affected the moulting rate, weight gain, shell length and width and the survival of mud crabs. The best treatment was found in the 5.50 ml treatment with a molting rate of 16 days, weight gain of 12.09 grams, length of 1.84 cm, width of 7.33 and survival rate of 100%. The water quality during the study showed that it was still in a good range or can be tolerated by mangrove crabs, the water quality range was temperature 26.5-27 oC, pH 7.0-8.0, DO 6.3-6.8 mg, and salinity 34 - 35 ppt.Keywords: Ecdysteroids; Growth; Mangrove Crab; Moulting; Reproduction.